Hydrotubation: Combined Technique: more fluid intrauterine surgery - Medina Cardozo, Juan F (Revista Universidad de Guayaquil, 2014)
The objective of this work is to expose the medical community a technique of Hidrotubation less aggressive, more economical and practical to solve infertility caused by tubal obstruction postsurgical. For many years dating back to the last century physicians have been practicing some surgical techniques and the application of intrauterine substances in order to “un-cork” the(s) tube(s) of Fallopian with flattering results slightly. The technique consists of a combined procedure of pelvic laparotomy and intrauterine application vaginally of distilled water, corticosteroids and mucolytic that at the time this giving successful outcomes for the treatment of tubal infertility cause. The innovations that have been demonstrated in this work are the product of many years of persistent practice and private experience in the treatment of obstructive tubal pathology strictly in the surgical field and the drug aspect will be a significant contribution to the improvement of the technique hydrotubation in our midst. In this work I expose a case of post-surgical tubal obstruction was resolved by applying this technique conservative and had a happy ending, sought success pregnancy, live birth in good condition, happiness mother and partner. With this report, also demonstrate the benefit post - surgical instruments when applying less material in the region is operated and a matter of adaptation of the technique.